Adventures with Iphigenia in Tauris a cultural history of Euripides' Black Sea tragedy - Hall, Edith 1959- (Onassis series in Hellenic culture, 2013)
Human sacrifice, a spirited heroine, a quest ending in a hairsbreadth escape, the touching reunion of long-lost siblings and exquisite poetry - these features have historically made Euripides' 'Iphigenia in Tauris' one of the most influential of Greek tragedies. With this book, Edith Hall provides a much-needed cultural history of this play, giving as much weight to the impact of the play on subsequent Greek and Roman art and literature as on its manifestations since the discovery of the sole surviving medieval manuscript in the 1500s